Mechanistic Insights into the Bornyl Diphosphate Synthase from Lavandula angustifolia - Dafeng Liu; Na Li; Feng Yu; Yanyan Du; Hongjun Song; Wenshuang Yao (Current Issues in Molecular Biology)
Lavender species hold substantial economic importance due to their widespread cultivation for essential oils (EOs). Lavender EOs contain terpenes essential for industries such as cosmetics, personal care, and pharmaceuticals. In the biosynthetic pathway of EOs, Lavandula angustifolia bornyl diphosphate synthase (LaBPPS) catalyzes the conversion of geranyl diphosphate (GPP) to bornyl diphosphate (BPP). However, the functional mechanisms of LaBPPS remain poorly understood. Here, we conducted mutational experiments based on the molecular docking results, and found that mutations at positions D356A, D360A, R497A, D501A, or E508A led to a 50- to 100-fold reduction in the activity. Deletion of region 1–58 (∆1–58) did not affect activity compared to the wild-type (WT) protein, while deletions of regions 1–74 or 59–74 (∆1–74 or ∆59–74) significantly decreased the activity. Conversely, deletion of residues 578–602 (∆578–602) dramatically increased the activity. The LaBPPS gene showed dramatically higher expression levels in flowers compared to other tissues (stems, leaves and roots), peaking at 8:00. Our results provide valuable insights into EO biosynthesis in lavender and suggest potential strategies for genetic engineering aimed at improving EO quality.